THE EFFECTIVENESS OF WOMEN ON BOARDS IN AFFECTING ISLAMIC SOCIAL REPORTING DISCLOSURE - LATIFAH SUKMAWATI YUNIAR; ANDI AINIL MUFIDAH TANRA; ANDI CHAIRIL FURQAN (Maqdis: Jurnal Kajian Ekonomi Islam, 2022)
This study investigates the potential impact of gender diversity on the Islamic social reporting disclosure of Indonesian sharia-approved firms. These firms operate in accordance with Islamic principles and have been approved by regulators. The study uses quantitative analysis and regression models to analyze data from a sample of firms listed in the Jakarta Islamic Index between 2016-2018. The findings suggest that having women on the board of directors and commissioners has a detrimental effect on ISR disclosure, possibly due to the lack of adequate representation of women on boards. This study contributes to the ongoing discourse about the relationship between gender diversity in corporate leadership and social responsibility in Islamic businesses.